Synthesis and Electrochemical Reaction Mechanism of Zn-TiOx-C Nanocomposite Anode Materials for Li Secondary Batteries. Issue 12 (1st January 2017) - Choi, Hyerang; Kim, Kyungbae; Cho, Woosuk; Park, Cheol-Min; Kim, Jae-Hun
Abstract : A nanocrystalline-Zn-embedded TiO x –amorphous carbon composite was prepared using a two-step high-energy mechanical milling (HEMM) process. First, the starting ZnO was reduced to Zn by Ti incorporation via HEMM. The resulting Zn–TiO x composite was then placed in an amorphous carbon matrix via a second milling step, resulting in a Zn–TiO x –C nanocomposite. The samples were analyzed by X-ray diffraction (XRD), Raman spectroscopy, and X-ray photoelectron spectroscopy; the results confirmed the formation of metallic Zn and amorphous TiO x phases in the composite. The nanocrystalline-Zn-embedded phase and its distribution were observed by high-resolution transmission electron microscopy. The electrochemical reaction mechanism of the Zn–TiO x –C nanocomposite with Li + during the first cycle was investigated by ex situ XRD analysis. The results demonstrated the reaction sequence of the nanocrystalline Zn phase with Li + and the electrochemical reactivities of the amorphous TiO x and carbon phases toward Li + . In the electrochemical tests, the Zn–TiO x –C composite showed greatly improved electrochemical properties compared to those of pure Zn. This improvement was attributed to the microstructure of the composite, in which the nanocrystalline Zn was uniformly dispersed, to the TiO x phases, and to the amorphous carbon matrix functioning as buffers against the large volume changes of Zn.